Endobronchial Leiomyoma Presenting as Post‐Obstructive Pneumonia - Boon Hau Ng; Hsueh Jing Low; Nik Nuratiqah Nik Abeed; Nor Safiqah Sharil; Rose Azzlinda Osman; Maalini Krishnasamy; Andrea Yu‐Lin Ban; Jamalul Azizi Abdul Rahaman (Respirology Case Reports)
ABSTRACT Endobronchial leiomyoma is a rare airway tumour. We report the case of a 30‐year‐old female non‐smoker who presented with persistent fever and cough, ultimately diagnosed with post‐obstructive pneumonia secondary to an endobronchial leiomyoma. The patient underwent a successful endobronchial cryo‐resection with the resolution of symptoms. This case highlights the importance of considering rare causes of non‐resolving pneumonia and the role of a minimally invasive approach in the management of endobronchial leiomyoma.